EFFECTS OF SAGO-BASED (Metroxylon sagu) CARBOHYDRATEON GROWTH PERFORMANCE AND BLOOD PLASMA COMPOSITIONSOF NILE TILAPIA, Oreochromis niloticus (LINNAEUS, 1758) JUVENILES - Benny Lawrence, Senawi; Roslianah, Asdari; Mohammad Bodrul, Munir (Penerbit UMT, 2020)
Six diets were formulated with three levels of protein, P(22%, 26% and 30%), andtwolevelsofsagostarchassourceofcarbohydrates,C(38%and44%).Thedietswere fedtotriplicategroupsoftilapia,Oreochromisniloticus,juveniles(meanweight4.61±0.04 g), to apparent satiation twice daily for 12 weeks. Fish fed the 38% sago starch diet have a higher (P < 0.05) growth than the 44% sago starch and control diets. The whole body proximate compositions were significantly (P < 0.05) affected by the 38% and 44% dietarysagostarchlevelamongalldiets.Fishfedwith38%sagostarchdietshaveahigher (P < 0.05) glucose concentration in plasma than those fed with diet containing the 44% group diets. Higher (p < 0.05) triglyceride plasma were observed in fish fed with the 44% level diets, compared with the other diets. Two-way ANOVA results confirmed that the interaction between protein and carbohydrate has a significant (p < 0.05) influenced on growthperformance,whole-bodyproximatecompositionsandbloodplasmacompositions. The study revealed the ability of O. niloticus juvenilesto spare protein by carbohydrate at the level of 38 % sagostarch